Characteristic Study of Knowledge and Behaviour of Housekeeping on Office Staff - Merry Andrianti; Y. Denny A. Wahyudiono (Universitas Airlangga, 2022)
Introduction: Housekeeping behavior is a process of behavior change by applying workplace hygiene and arrangement. This research was conducted to determine the strength of the factors associated with housekeeping behavior on employees in the Situbondo District Health Office. This research was conducted to analyze the relationship of knowledge, attitudes, and supervision with the application of housekeeping behaviour on employees at the Situbondo District Health Office. Methods: This research was a cross-sectional study. The location of this research was in the Situbondo District Health Office. Primary data collection was carried out in April 2020, and the number of samples was 50 civil servants in the Situbondo District Health Office. This study used two kinds of variables, namely independent variables: age (X1), sex (X2), work period (X3), and education (X4), and dependent variables, namely knowledge of housekeeping (Y1) and behavior of housekeeping (Y2). The main research data were obtained from observations, surveys of housekeeping behavior factors, and observations of housekeeping behaviour . Moreover, the data analysis used a correlation analysis check. Results: The results showed that the work period and the knowledge of housekeeping had a relationship, but it was in a low influence with the sigma of 0.036 and correlation coefficient of 0.298. The results also showed that sex and the behavior of housekeeping had a relationship, but it was in a low influence with the sigma of 0.028 and correlation coefficient of 0.312. Conclusion: Work period had a relationship with housekeeping knowledge and sex had a relationship with the housekeeping behavior, but it was in a low influence.Keywords: characteristics, knowledge of housekeeping, behavior of housekeeping